1999
DOI: 10.1038/sj.bjc.6690294
|View full text |Cite
|
Sign up to set email alerts
|

Expression of the thymidine phosphorylase gene in epithelial ovarian cancer

Abstract: Summary Thymidine phosphorylase (TP) is associated with angiogenesis and the progression of solid tumours. High intracellular levels of this enzyme indicate increased chemosensitivity to pyrimidine antimetabolites. TP gene expression in 56 cases of epithelial ovarian cancer (27 of serous, 10 mucinous, 12 endometrioid, five clear cell and two undifferentiated) were analysed by polymerase chain reaction of RNA after reverse transcription. These included eight of low malignant potential. Twenty were stage I, four… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
20
0

Year Published

2000
2000
2009
2009

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 31 publications
3
20
0
Order By: Relevance
“…In experimental models, TP overexpression increased tumour cell invasion (Ueda et al, 2001) and tumorigenicity (Griffiths and Stratford 1998;Brown et al, 2005). In man, high tumour expression of TP generally correlates with a poor prognosis in various solid malignancies (Takebayashi et al, 1996;Ikeda et al, 1999) including cervix cancer (Fujimoto et al, 1999;Hata et al, 1999;Ueda et al, 1999). However, this finding is not universal, as one study in cervix cancer showed that high tumour TP positivity was associated with a good prognosis (Oka et al, 2003).…”
mentioning
confidence: 63%
“…In experimental models, TP overexpression increased tumour cell invasion (Ueda et al, 2001) and tumorigenicity (Griffiths and Stratford 1998;Brown et al, 2005). In man, high tumour expression of TP generally correlates with a poor prognosis in various solid malignancies (Takebayashi et al, 1996;Ikeda et al, 1999) including cervix cancer (Fujimoto et al, 1999;Hata et al, 1999;Ueda et al, 1999). However, this finding is not universal, as one study in cervix cancer showed that high tumour TP positivity was associated with a good prognosis (Oka et al, 2003).…”
mentioning
confidence: 63%
“…24,26 The relative risk of cancer death from tumors with high expression of the TK1, TS and TP genes was greater than the risk from tumors with high expression of any of these genes alone. Although expression of each of these genes alone was not an independent prognostic factor by multivariate analysis, the combined gene expression status of these 3 enzymes was an independent predictor of survival.…”
Section: Relationship Between Expression Of the Tk1 Ts And Tp Genes mentioning
confidence: 99%
“…23,24,26 Levels of TS, TP and DPD gene expression were reported in most patients with malignant ovarian tumors and normal ovaries.…”
Section: Conventional Rt-pcr For Tk1 Gene Expressionmentioning
confidence: 99%
See 2 more Smart Citations